2007
DOI: 10.1177/0165551506070733
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the determinants of knowledge transfer: a team-level analysis

Abstract: The research area of knowledge transfer is a critical one in the current era of the knowledge economy. Previous studies have channelled much effort into understanding how knowledge transfer could be facilitated efficiently. Yet most of these studies conducted research only at the individual level, ignoring the fact that, in many organizations, the team now serves as the basic unit for transferring and preserving knowledge. In addition, these studies have not put much emphasis on the learning side of knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 42 publications
(49 reference statements)
5
72
0
1
Order By: Relevance
“…Lewis and Weigert (1985) outlined two different ways that trust can be formed: cognitive trust which is formed on 'good rational reasons' of trustworthiness, and affective trust which refers to the emotional bonds between truster and trustee. Both cognitive and affective trust encourages information-sharing at dyadic and team levels (Chowdhury 2005;Mooradian, Renzl, and Matzler 2006;Wu, Hsu, and Yeh 2007). Xu, Li, and Shao (2012) further found that cognitive trust and affective trust can predict voluntary knowledge-sharing behaviour in online communities.…”
Section: Interpersonal Trust In Online Information-sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis and Weigert (1985) outlined two different ways that trust can be formed: cognitive trust which is formed on 'good rational reasons' of trustworthiness, and affective trust which refers to the emotional bonds between truster and trustee. Both cognitive and affective trust encourages information-sharing at dyadic and team levels (Chowdhury 2005;Mooradian, Renzl, and Matzler 2006;Wu, Hsu, and Yeh 2007). Xu, Li, and Shao (2012) further found that cognitive trust and affective trust can predict voluntary knowledge-sharing behaviour in online communities.…”
Section: Interpersonal Trust In Online Information-sharingmentioning
confidence: 99%
“…Hsu et al (2007) and Hsu, Chang, and Yen (2011) found that interpersonal trust is an effective predictor of knowledge-sharing behaviour in professional societies. Wu, Hsu, and Yeh (2007) explained that trust is a determinant of information-sharing because the sharing activity involves providing information and knowledge to another person or a collective with expectations for reciprocity. Abrams et al (2003) distinguished between competence trust (confidence in the trustee's ability) and benevolence trust (faith in the trustee's trustworthy intentions) and argued that both of them enable effective knowledge creation and sharing in organisational networks.…”
Section: Interpersonal Trust In Online Information-sharingmentioning
confidence: 99%
“…Many previous researchers have stated that a company should offer their employees a good knowledge-sharing environment to encourage and enhance their knowledge-sharing behavior (e.g., Davenport & Prusak, 1998;Nonaka & Takeuchi, 1995;Wu, Hsu, & Yeh, 2007). Wu et al noted that the company could set up social interaction activities to encourage members to learn from and share with one another.…”
Section: Friendly Knowledge-sharing Environmentmentioning
confidence: 99%
“…First, the conduct of the knowledge sharing necessarily involves the interaction of knowledge sharers and learners, such as the exchange of views by chatting. In addition, this social exchange behavior needs a good knowledge-sharing platform (Wu et al, 2007). However, because it is often assumed that when employees are chatting, they are slacking in their work, companies often try to prohibit such chatting.…”
Section: Friendly Knowledge-sharing Environmentmentioning
confidence: 99%
“…Examining trust and justice is important because knowledge-sharing involves providing knowledge to another person or a collective unit, such as a team or community of practice with expectations for reciprocity (e.g., [73]). Research has shown that affect-and cognition-based trust have a positive influence on knowledgesharing at the dyadic and team levels [16,44,73]. On the basis of these studies, we proposed the following hypotheses:…”
Section: Trust and Knowledge-sharingmentioning
confidence: 99%